SYNTHESIS AND CHARACTERIZATION IN VITRO ANTIMICROBIAL AND CYTOTOXICITY TESTING OF OXALIC ACID-DERIVED CADMIUM CHELATING AGENTS - F, Daisy Selasteen; S, Alfred Cecil Raj; A, Alagappa Moses (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: The aim of this study is to investigate the growth, structure, spectral, solubility and biological activity of sodium cadmium oxalate dehydrate (NaCdOx) and cadmium oxalate trihydrate (CdOx) crystals prepared by a single diffusion method in the silica gel medium. Methods: The present crystals were grown using single diffusion methods and tested for XRD, UV absorption (190 to 1100 mm) and solubility (distilled water at 20-29 Â°C) studies. The antimicrobial efficacy of the grown samples at various concentrations (25, 50, 75 and 100 Î¼g/ml) was studied against Streptococcus, (G+Ve), Pseudomonas aeruginosa (G-Ve) and Candida albicans (antifungal). The cytotoxicity evolution was carried out against human cervical cancer cell line (HeLa) using MTT assays. Results: The existing single crystals were successfully grown by silica gel technique. The solubility of sodium cadmium oxalate dehydrate (NaCdOx) was moderately good in deionized warm water. The FTIR spectral studies confirmed the chelating bands of the present samples and UV spectra showed the better the optical conductivity of as-grown crystals. The complexes showed good antimicrobial activity against all tested microbial strains and they exhibited a decrease in cytotoxicity activity. Conclusion: The gel method was suitable to grow metal complexes of legend crystals. The modification of structural properties of cadmium oxalate trihydrate (CdOx) by sodium doping was much improved the solubility, anticancer, antimicrobial activity and polarization by the high optical conductivity of sodium cadmium oxalate dehydrate (NaCdOx) compound. Hence sodium cadmium oxalate dehydrate (NaCdOx) might be a candidate for biomedical applications. Â 